2022
DOI: 10.1021/acsami.2c16142
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Enhanced Energy Storage Performance in High Hardness BKT-Based Ceramic via Defect Engineering and Relaxor Tuning

Abstract: Hybrid electric cars and pulsed power technologies have increased the demand for capacitors with high energy density, wide temperature stability, high operating voltage, and good mechanical qualities. In this work, (1 − x) (0.6Bi 0.5 K 0.5 TiO 3 -0.4BiFeO 3 )-x(Na 0.4 Sm 0.2 NbO 3 ) ((1 − x) (BKTBF)-xNSN) relaxor ceramics were prepared by constructing morphotropic phase boundary (MPB) combined with oxygen vacancy defect engineering. It is worth noting that the 0.6BKT-0.4BFO ceramics at MPB have a high P max ∼ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 69 publications
(115 reference statements)
1
11
1
Order By: Relevance
“…Encouragingly, a giant W rec of 17.3 J cm –3 , together with a high η of 88.5%, is realized under an E B of 78 kV mm –1 (Figure e). In comparison, the W rec in BKT-D1 exceeds the previously reported highest value in BKT-based systems, , which was 7.6 J cm –3 in BKT-BT-NN, by more than double (Figure f and Table S3). Moreover, the energy storage properties well outperform other lead-free bulk ceramics, such as BT-based, BNT-based, NN-based, and AN-based RFEs (Figure S6).…”
Section: Resultscontrasting
confidence: 48%
See 1 more Smart Citation
“…Encouragingly, a giant W rec of 17.3 J cm –3 , together with a high η of 88.5%, is realized under an E B of 78 kV mm –1 (Figure e). In comparison, the W rec in BKT-D1 exceeds the previously reported highest value in BKT-based systems, , which was 7.6 J cm –3 in BKT-BT-NN, by more than double (Figure f and Table S3). Moreover, the energy storage properties well outperform other lead-free bulk ceramics, such as BT-based, BNT-based, NN-based, and AN-based RFEs (Figure S6).…”
Section: Resultscontrasting
confidence: 48%
“…The energy storage capacity of a dielectric material is determined by its polarization traits and breakdown strength ( E B ). Lead-free relaxor-ferroelectric (RFE) solid solutions exhibit desirable merits of large polarization ( P m ) and small hysteresis ( H ), making them the preferred option for high-performance dielectric capacitors. Owing to the high chemical flexibility of perovskites that allow for various atomic combinations at both A- and B-sites, substantial lead-free RFEs have been explored to optimize energy-storage performance. , Examples include BaTiO 3 (BT)-based, ,, Bi 0.5 K 0.5 TiO 3 (BKT)-based, SrTiO 3 (ST)-based, , Bi 0.5 Na 0.5 TiO 3 (BNT)-based, ,, (K,Na)­NbO 3 (KNN)-based, , NaNbO 3 (NN)-based, , and AgNbO 3 (AN)-based ,, relaxors, and their corresponding W rec in bulk ceramics has been significantly improved, with values typically ranging from 4 to 8 J cm –3 .…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that as the electric field increases from 60 to 260 kV/cm, the W d value shows a linear growth from 0.2281 to 1.549 J/cm 3 .The parameter τ 0.9 used to estimate the discharge time is determined to be 132 ns, demonstrating a relatively fast discharge speed. A comparison of the charge–discharge performance of the BKBSC-0.2Cu ceramic with those of other documented energy storage ceramics is shown in Figure (d). ,,,, Clearly, the C D and P D of the BKBSC-0.2Cu ceramic are better than those of many reported lead-free dielectric ceramics.…”
Section: Resultsmentioning
confidence: 95%
“…These results indicate the immense energy storage capacity of the BKBSC-0.2Cu high-entropy ceramic. To comprehensively assess the energy storage capacity, we compared the various properties of recently published representative high-entropy ceramics, , BKT-based ceramics, BNT-based ceramics, KNN-based ceramics, and NN-based ceramic, as shown in Figure (e) (see Table S4 for details). It is clear that the BKBSC-0.2Cu ceramic exhibits superior characteristics in W rec , ε r , P max , E b , and η, especially in terms of maintaining a high breakdown electric field and high dielectric constants, which offer significant advantages compared to other ceramics.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, the larger Δ P (Δ P = P m – P r ) at the highest possible breakdown field strength ( E b ), the larger the W rec can be obtained. Dielectric ceramic capacitor materials, such as BaTiO 3 , SrTiO 3 , Bi 0.5 K 0.5 TiO 3 , and K 0.5 Na 0.5 NbO 3 with ultrahigh energy storage density, great temperature, frequency stability, and terrific mechanical strain properties, have caught the attention of researchers over the past decade. For instance, Li et al reported a W rec = 6.52 J cm –3 with η = 70% under 425 kV cm –1 in 0.84­(0.6 Bi 0.5 K 0.5 TiO 3 -0.4BiFeO 3 )-0.16­(Na 0.4 Sm 0.2 NbO 3 ). Du et al achieved a W rec of 4.08 J cm –3 under 300 kV cm –1 by incorporating Bi­(Mg 2/3 Nb 1/3 )­O 3 into the K 0.5 Na 0.5 NbO 3 ceramic.…”
Section: Introductionmentioning
confidence: 99%